Pemberdayaan Kader Kesehatan Melalui Program Pembinaan Fisik Lansia Untuk Meningkatkan Kemampuan Fungsional Tulang Belakang - Cica Tri Mandasari; Muhammad Fathi; Muh Syaiful Akbar; Isnaini Qoriatul Fadhilah (Indonesian Journal Publisher, 2023)
Spinal health is very important for carrying out daily activities. The functional abilities of the spine can experience problems both in adolescents and in adults to the elderly. However, the decrease in functional ability increases with age and often occurs in the elderly. Empowerment of cadres can be one of the solutions in preventing this functional decline. In this community service, empowerment of health cadres will be carried out, namely education and prevention in improving the functional abilities of the spine. In addition, they also received training on how to carry out simple detection of spinal diseases in the elderly. The education provided includes providing knowledge about spinal activities that are not too burdensome to the functional spine. In addition, through regular sports activities by providing stretching in the spinal area to improve spinal function. Thus, community service activities are expected to be used as a means of developing and applying direct knowledge to the community by lecturers.Written in English with a distance between sentences of 1 space and the number of words between 150-250. The abstract should contain introductions, methods, results and discussions and conclusions (without citation). Avoid using citations in the abstract.